Unwillingness to Communicate in Survival English Course: Evidence from Indonesian EFL Students - Sri Mulyani; Fuad Abdullah; Ruslan Ruslan; Arini Nurul Hidayati; Agis Andriani; Soni Tantan Tandiana (English Department - University of Sultan Ageng Tirtayasa, 2023)
Willingness to Communicate (WTC) has been extensively scrutinized over the last few decades. However, although there has been much research focusing on WTC, a few studies explored the students' unwillingness to communicate (UWTC) and its influential factors, notably in Indonesian higher education. Hence, the present study aims to delineate the students' UWTC and its influential factors while learning English speaking in the Survival English Course. Six English Education Department students of a state university in Tasikmalaya, West Java, Indonesia took part as investigative participants. Data was collected through semi-structured interviews and analyzed thematically. The findings revealed that students tended to indicate UTC while learning English speaking in the Survival English Course. In addition, the factors influencing their WTC encompassed students' less self-confidence, students' learning anxiety, demotivated to speak English, classroom atmosphere, unintelligible pronunciation, and uninteresting topics. Given these facts, understanding the students' UWTC and its influential factors enables the teacher to apply appropriate teaching methods, instructional media, and teaching materials coherently. By doing so, the students' UWTC can be mitigated and transformed to be WTC.